THE COMPARATIVE ANALYSIS OF THE 3-IN-1 AND ODD-EVEN POLICIES IN EFFORTS TO CONTROL TRAFFIC CONGESTION IN JAKARTA - Ammar Musaddad Thariq; Ridwan, Ridwan (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study examines a comparative analysis between the 3-in-1 and Odd-Even traffic policies implemented in Jakarta as efforts to control congestion in the city. The main problem addressed is the ineffectiveness and sustainability of these traffic restriction systems in reducing congestion over time. The purpose of this research is to identify the differences in regulation, implementation mechanisms, outcomes, and advantages-disadvantages between the two policies. Using a qualitative descriptive method supported by document analysis, literature review, and interview results, the study evaluates both policies through the theoretical framework of Dye (2013), Sabatier and Jenkins-Smith (1993), and Grindle (1980). The findings indicate that the Odd-Even policy is more effective and transparent due to the integration of electronic enforcement systems and measurable environmental benefits, while the 3-in-1 policy, though initially simple and cost-efficient, faced issues of misuse and low compliance. The study concludes that technological integration and public participation are key to improving the sustainability of traffic management policies in Jakarta.